2011
DOI: 10.1111/j.1551-2916.2011.04917.x
|View full text |Cite
|
Sign up to set email alerts
|

The Antiferroelectric ↔ Ferroelectric Phase Transition in Lead‐Containing and Lead‐Free Perovskite Ceramics

Abstract: A comprehensive review on the latest development of the antiferroelectric ferroelectric phase transition is presented. The abrupt volume expansion and sudden development of polarization at the phase transition has been extensively investigated in PbZrO 3 -based perovskite ceramics. New research developments in these compositions, including the incommensurate domain structure, the auxetic behavior under electric fields in the induced ferroelectric phase, the ferroelastic behavior of the multicell cubic phase, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
246
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 363 publications
(257 citation statements)
references
References 175 publications
(464 reference statements)
11
246
0
Order By: Relevance
“…9 Since then, even higher strains (0.48%) have been reported, [12][13][14][15] primarily in modified [Bi 1/2 (Na 1-x K x ) 1/2 ]TiO 3 compositions. 16,17 These values are higher than those measured in piezoelectric Pb(Zr 1Àx Ti x )O 3 and electrostrictive Pb(Mg 1/3 Nb 2/3 )O 3 -based ceramics, and are believed to trace their origin to the unique P4bm relaxor ferrielectric phase [18][19][20] in the base compound (Bi 1/2 Na 1/2 )TiO 3 . Under applied electric fields, the relaxor phase, with nanometer-sized domains, transforms into the ferroelectric phase, with micrometer-sized domains.…”
mentioning
confidence: 54%
“…9 Since then, even higher strains (0.48%) have been reported, [12][13][14][15] primarily in modified [Bi 1/2 (Na 1-x K x ) 1/2 ]TiO 3 compositions. 16,17 These values are higher than those measured in piezoelectric Pb(Zr 1Àx Ti x )O 3 and electrostrictive Pb(Mg 1/3 Nb 2/3 )O 3 -based ceramics, and are believed to trace their origin to the unique P4bm relaxor ferrielectric phase [18][19][20] in the base compound (Bi 1/2 Na 1/2 )TiO 3 . Under applied electric fields, the relaxor phase, with nanometer-sized domains, transforms into the ferroelectric phase, with micrometer-sized domains.…”
mentioning
confidence: 54%
“…), polarization magnitude P (µC/cm 2 ), estimated equilibrium strain for the (001)C (σc) and (100)C (σa) matching planes, and volume expansion ∆V /V (%) of selected polar structures. ferroelectric phase [11].…”
Section: Figmentioning
confidence: 99%
“…Despite extensive studies and characterization, PZO continues to offer insights into the origin and complexity of antiferroelectricity [10,11]. In bulk form, PZO has a cubic perovskite structure at high temperatures and a nonpolar orthorhombic ground state below T c ∼ 505 K. The ground state has space group Pbam [12, 13] and unit cell dimensions √ 2a 0 × 2 √ 2a 0 × 2a 0 with respect to the reference lattice constant a 0 .…”
mentioning
confidence: 99%
“…[2][3][4][5][6][7][8] Most studied antiferroelectric ceramics in literature are based on the prototype compound PbZrO 3 with a perovskite structure, in which the phase transition manifests itself in the development of a large polarization and is generally accompanied by a significant volume expansion when the applied field exceeds a critical magnitude E F . [2][3][4][5][6][7][8][9][10] The associated volume change at the phase transition has been explored as a mechanism for toughening the ceramic. 11 Recently, it has been reported that some chemically modified PbZrO 3 -based ceramics can exist either in the antiferroelectric or ferroelectric state at room temperature, depending on their thermal history.…”
mentioning
confidence: 99%